Dynamics of the corotating vortices in dipolar Bose-Einstein condensates in the presence of dissipation - Gautam, S. (Iop Publishing Ltd, 2014)
We study the dynamics of a single and a corotating vortex pair in a dipolar Bose-Einstein condensate in the framework of a dissipative Gross-Pitaevskii equation. This simple model enables us to simulate the effect of finite temperature on the vortex dynamics. We study the effect of dipolar interactions on the dynamics of a single vortex in the presence of phenomenological dissipation. In the case of a corotating vortex pair, initial asymmetry in the locations of the vortices can lead to different decay rates for the constituent vortices, as is the case for the condensates interacting via pure contact interactions. We observe that the anisotropic interaction between the component vortices manifests itself as the perceptible difference in the trajectories traversed by the vortices in the condensate at finite temperatures.
Keywords: dipolar condensates; vortex dynamics; finite temperature